ASOSIASI BURUNG JULANG SULAWESI (Rhyticeros Cassidix) DENGAN JENIS â€“ JENIS POHON DI KAWASAN HUTAN LINDUNG DESA ENSA KEC. MORI ATAS KAB. MOROWALI UTARA - Bamotiwa, Daniel; Labiro, Elhayat; Ihsan, Moh. (Jurnal Warta Rimba, 2014)
Rangkong (Famili Bucerotidae) often known as allo bird by people is ripe fruit specialit. There is about 69% of its food containing Ficus fruit in breeding season. Association rafers to dependant of one type to another either animal or plant from the low to the high. This reserch aims to find out rangkong association of sulawesi (famili bucerotidae) with tree types of preservation forest area in ensa village. The data were collected through primary and secondary data. The presence of each species will be noted on amount of plot and then it will be put intoÂ  contingence table 2 x 2. The result can be proved by using table X2 . the result depends on the plot size because the data comes from the presence frequency. To fine out the is association or not between two types, comparison of Chi-square X2 counted with X2 table on degree of freedom = 1.Based on the result by making 25 plots of observation, rangkong was found on 14 observation plots and the analysis result of rangkong species of sulawesi (Rhyticeros cassidix) with tree types on the preservation forest is 15 trees and indicating positive relationship or associate with 3 tree types of association value X2 counted namely beringin (11.9141), nantu (4.3388) and malapoga (4.956995). Keywords : Birds Association, Knobbeed Hornbill (Rhyticeros cassidix) Tree Ensa Village.